2018
DOI: 10.1186/s13052-018-0567-9
|View full text |Cite
|
Sign up to set email alerts
|

Dietary diversity feeding practice and its associated factors among children age 6–23 months in Ethiopia from 2011 up to 2018: a systematic review and meta-analysis

Abstract: BackgroundGlobally Less than one fourth of children aged 6–23 months get the recommended minimum dietary diversity feeding practice. Despite this issue is common in Ethiopia, fragmented and inconsistent findings were found. Therefore the main objective of this meta-analysis was to estimate the pooled prevalence of dietary diversity feeding practice and to identify its associated factors among children aged 6–23 months in Ethiopia.MethodsThe Preferred Reporting Items for Systematic Reviews and Meta-Analyses gui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
43
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(68 citation statements)
references
References 27 publications
19
43
2
Order By: Relevance
“…Mothers who had ANC and PNC follow up were more likely to provide diversified diet to their children. This finding is supported with other study in Ethiopia (18,19). ANC and PNC follow up may supported with nutrition education, which is a very important input to help people to select an adequate and variety of diet.…”
Section: Discussionsupporting
confidence: 88%
“…Mothers who had ANC and PNC follow up were more likely to provide diversified diet to their children. This finding is supported with other study in Ethiopia (18,19). ANC and PNC follow up may supported with nutrition education, which is a very important input to help people to select an adequate and variety of diet.…”
Section: Discussionsupporting
confidence: 88%
“…Additionally, one article was found by hand searching of the reference lists of the included studies. Thus, a total of 9 studies [4,[22][23][24][25][26][27][28][29] were included in the current umbrella review. The study selection and screening process is shown in Fig.…”
Section: Literature Search Findingsmentioning
confidence: 99%
“…Health [22][23][24][26][27][28][29] Lack of antenatal care Lack of postnatal care Place of delivery Sociodemographic [22][23][24][26][27][28][29] [26][27][28][29] Place of residence IYCF, Infant and young child feeding.…”
Section: Risk Factors Malnutritionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, one article was found by hand searching of the reference lists of the included studies. Thus, a total of 9 studies [4,[16][17][18][19][20][21][22][23] were included in the current umbrella review. The study selection and screening process is shown in Fig.…”
Section: Literature Search Ndingsmentioning
confidence: 99%